Exercise, athletes and allergies - Sorace, P. (Strength and Conditioning Journal, 2008)
Allergeis can affect athletes and clients in a number of ways. Some allergies (e. g. Rhinitis) can decrease quality of life and impair athletic performance. Other allergies ( e. g. exercise-induced Anaphylaxis) can be life-threatening. This column discusses some of the more common allergies and how to manage them so that quality of life and pyhsical performance are not negatively affected.